Self-Reported Sleep Quality Across Age Modulates Resting-State Functional Connectivity in Limbic and Fronto-Temporo-Parietal Networks: An Exploratory Cross-Sectional fMRI Study - Federico, Giovanni; Alfano, Vincenzo; Garramone, Federica; Mele, Giulia; Salvatore, Marco; Aiello, Marco; Cavaliere, Carlo (Frontiers in Aging Neuroscience, 2022)
Sleep problems are increasingly present in the general population at any age, and they are frequently concurrent with – or predictive of – memory disturbances, anxiety and depression. In this exploratory cross-sectional study, fifty-four healthy participants recruited in Naples (Italy; 23 females; mean age = 37.1 years, range = 20–68) completed the Pittsburgh Sleep Quality Index (PSQI) and a neurocognitive assessment concerning both verbal and visuospatial working memory as well as subjective measures of anxiety and depression. Then, 3T fMRI images with structural and resting-state functional sequences were acquired. A whole-brain seed-to-seed functional connectivity (FC) analysis was conducted by contrasting good (PSQI score < 5) vs bad (PSQI score >= 5) sleepers. Results highlighted FC differences in limbic and fronto-temporo-parietal brain areas. Also, bad sleepers showed an anxious/depressive behavioural phenotype and performed worse than good sleepers at visuospatial working-memory tasks. These findings may help to reveal the effects of sleep quality on daily-life cognitive functioning and further elucidate pathophysiological mechanisms of sleep disorders.